On the question of classification of rat’s ovarian follicles. - Hryhorieva, O. A.; Kovalchuk, K. S. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Ovaries, as part of the female reproductive system, play an important role in the normal and adequate functioning of the body. The reproductive systemare sensitive to the effects of environmental factors.Among frequent causes of defection in ovarian structure and functions are factors of different backgrounds, and above all - the effect of these factors on the formation of the reproductive system during pregnancy.After all, the fetal period is one of the critical periods of the morphosis.During the pregnancy period female sex hormones are widely used, in particular, progesterone - a hormone of the corpus luteum, which performs a number of important functions and is essential for the normal pregnancy course.So the consequences of intrauterine affection of progesterone on morphogenesis and fetal ovarian functioninghave not been sufficiently studied. One of the methods for the morphofunctional status of the ovaries assessment is to calculate and to determine the ratio of follicles at different stages of development.Most part of the publications considering the study of the structure of the follicles and their distribution occurred at the end of the twentieth century. As the basis of proposed classifications of follicles different parameters were taken - diameter of the follicle, the ratio of the diameter of the follicle to the number of follicular cells, the structure of the follicle.Objective. To determine the most convenient classification of rat ovarian follicles. Methods. Literature data was analyzed,including the International Histological nomenclature. Results. The classifications were characterizedand the conclusions were drawn about their practical significancefor studying the processes of folliculogenesis, especially after the action of various factors.Conclusion. The investigationof morphofunctional featuresof follicles according to various criteria helps to assess in more detail the changes in their structure and functioning and to identify possible pathological changes after the. various factors impact, in particular – hormones.